PENDAMPINGAN PEMBUATAN SENSOR KESEGARAN BUAH PADA SANTRI PUTRI DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO - Ningsih, Venny Diah; Nurrosyidah, Siti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Plants in Indonesia can be used for traditional medicine, dyes, and as natural chemical indicators. This natural chemical indicator has a higher level of safety than synthetic chemical indicators such as phemolphthalein, methyl orange, methyl red, bromothymol blue.Examples of plants that can be used as natural chemical indicators are purple sweet potatoes, red beets, hibiscus flowers, rosella flowers, four o’clock flowers, and red cabbage. Several sellers at the market for female students in the central area of the Salafiyah Syafi’iyah Sukorejo Islamic Boarding School sell several types of cut fruit which makes it easier for female students to consume cut fruit. When consuming cut fruit, you need to be careful because it is not certain that the cut fruit being sold is still fresh. Based on this, it is necessary to provide assistance in making fruit freshness sensors for female students.